QOE ESTIMATION BASED ON QOS MEASUREMENT FOR REAL-TIME VIDEO IN WIRELESS NETWORKS - PELEH, PETRO (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This article focuses on examining the challenge of assessing User Experience Quality (QoE) in the context of real-time video and other services in wireless networks. The research entails an analysis of three methodological models aimed at determining QoE based on measurements of Quality of Service (QoS). The first model explores the correlation between network bandwidth and user satisfaction, emphasizing the identification of an optimal bandwidth level to ensure the required quality of real-time video transmission. The second model investigates the impact of latency on users’ video perception, identifying critical latency points and proposing optimization strategies to enhance the network’s response to real-time demands. The third model concentrates on error resilience in data transmission and its influence on QoE. By examining error detection and correction methods, the authors consider possibilities to improve network reliability and ensure seamless video playback. The interaction of these three models allows the article’s authors to adopt a comprehensive approach to QoE assessment in wireless networks. By analyzing QoS parameters and their relationship with user perception, the study makes a valuable contribution to understanding the factors influencing real-time service quality. The obtained results can be utilized to develop effective optimization strategies for networks and ensure a high-quality QoE for end-users.